2014
DOI: 10.1016/j.jcrs.2014.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fusional vergence amplitudes after laser refractive surgery for moderate myopia

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Han et al. () studied changes in fusional vergence amplitude and near point of convergence in moderate myopic subjects as a result of corneal refractive surgery. They found a postoperative transient decrease in near vergence amplitude, with stabilization and a return to preoperative values achieved 3 months after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Han et al. () studied changes in fusional vergence amplitude and near point of convergence in moderate myopic subjects as a result of corneal refractive surgery. They found a postoperative transient decrease in near vergence amplitude, with stabilization and a return to preoperative values achieved 3 months after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients who underwent corneal refractive surgery complained of visual fatigue symptoms such as blurred vision and short time of working distance in the early postoperative period, which affected the visual quality. Currently, studies have con rmed that the changes of binocular visual function and accommodation in the early postoperative period after LASIK, LASEK or PRK may be related to the early postoperative visual fatigue, due to the changes of refractive state, prism effect, wound healing, residual refractive error and other factors [4,[9][10][11]. As a new type of corneal refractive surgery that has emerged in recent years, and studies have found that the postoperative vision recovery time is longer than that of traditional LASIK because of different principles and operative techniques, and which may affect on binocular vision [6,7].…”
Section: (Fig 2)mentioning
confidence: 99%
“…In this study, we didn't nd any difference in BIFR or BOFR before and after SMILE surgery. However, Han et al, together with Rajavi et al observed that the break point and recovery point of BOFR decreased 1 week after refractive surgery, and returned to normal level 3 months after surgery [4,15]. Holland D and Kushner indicated persistent diplopia was observed in patients with high anisometropia preoperative.…”
Section: (Fig 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hashemi (2013) highlights hot the near poing of convergence and the near point of accommodation may increase significantly after photorefractive keratectomy (PRK) [2]. In 2014 Han reported an increase in the fusional vergence at near following refractive surgery [3]. Chung (2014) underlines the risk of a change in the ocular alignment, particulary in cases with a large-angle heterophoria/ heterotropia [4].…”
Section: Introductionmentioning
confidence: 99%